Interface shear behaviour of precast prestressed concrete beams with slebers webs in beam and slab construction - SLEVIN, MICHAEL (Trinity College Dublin. School of Engineering. Disc of Civil Structural & Environmental Eng, 2019)
All over the world precast prestressed concrete bridge beams are commonly used in small to medium sized highway and railway bridges, i.e. 20-50m spans. The majority of these bridges are built using I and U shaped precast prestressed concrete bridge girders with slender webs. When combined with a cast insitu deck slab they form a composite section that must be capable of resisting the horizontal shearing forces developed at the interface between the two elements. Interface shear requirements are generally more onerous than vertical shear when determining reinforcement ratios and this has become quite a contentious issue for bridge engineers in recent years with differing clauses in the design codes. This thesis presents work which examines the performance of thirteen 3.2m long reinforced concrete T-beams and seven 3.3m long beams dynamically and statically tested using a four point loading set-up with varying load and reinforcement ratios crossing the interface. The interface roughness and concrete strength does not vary as the parameters chosen are synonymous with bridge construction. The study also investigates the appropriateness for setting the cohesion factor c equal to zero for fatigue and dynamic verifications as per clause 6.2.5(105) of Eurocode 2 Part 2 (2005). The aim of the research was to propose a minimum interface shear reinforcement equation for incorporation into Eurocode 2 Part 1-1 (2004). It is recognised that a minimum percentage of reinforcement is required across the interface to prevent interfacial slip and brittle failure at loss of adhesion. Eurocode 2 Part 1-1 (2004) does not presently include a minimum requirement.
APPROVED
Keywords: Interface Shear; Horizontal Shear; Longitudinal shear; Prestressed concrete; Bridge beams